Defining the layers of a sensory cilium with STORM and cryoelectron nanoscopy - Robichaux, Michael A. (Proc Natl Acad Sci U S A, 2019)
Primary cilia carry out numerous signaling and sensory functions, and defects in them, “ciliopathies,” cause a range of symptoms, including blindness. Understanding of their nanometer-scale ciliary substructures and their disruptions in ciliopathies has been hindered by limitations of conventional microscopic techniques. We have combined cryoelectron tomography, enhanced by subtomogram averaging, with superresolution stochastic optical reconstruction microscopy (STORM) to define subdomains within the light-sensing rod sensory cilium of mouse retinas and reveal previously unknown substructures formed by resident proteins. Domains are demarcated by structural features such as the axoneme and its connections to the ciliary membrane, and are correlated with molecular markers of subcompartments, including the lumen and walls of the axoneme, the membrane glycocalyx, and the intervening cytoplasm. Within this framework, we report spatial distributions of key proteins in wild-type (WT) mice and the effects on them of genetic deficiencies in 3 models of Bardet–Biedl syndrome.